1978
DOI: 10.1159/000181428
|View full text |Cite
|
Sign up to set email alerts
|

Lysine in Treatment of Hyperornithinemia

Abstract: A metabolic study in a case of hyperornithinemia with gyrate atrophy of choroid and retina is presented. It is demonstrated that the lysine-ornithine antagonism is a physiological, safe, easy to handle therapeutic tool in hyperornithinemia. A lysine load was invariably associated with a reduction of plasma ornithine concentration. This happened at any level of protein intake. It was also shown that diets containing a low protein intake are invariably associated with negative nitrogen balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Unfortunately, the long term consequences of pyridoxine treatment in these patients have not been described. Several other experimental treatments, including supplementation with creatine or proline, failed to show unequivocal efficacy (21)(22)(23)(24). Attempts at correcting ornithine accumulation by dietary reduction of its precursor, arginine, have been described in several studies (Fig.…”
mentioning
confidence: 99%
“…Unfortunately, the long term consequences of pyridoxine treatment in these patients have not been described. Several other experimental treatments, including supplementation with creatine or proline, failed to show unequivocal efficacy (21)(22)(23)(24). Attempts at correcting ornithine accumulation by dietary reduction of its precursor, arginine, have been described in several studies (Fig.…”
mentioning
confidence: 99%
“…Care must also be taken to avoid negative nitrogen balance, which occurred in one child when the daily protein intake was 1 g/kg or less (11). Addition of non-essential nitrogen to the diet corrected this problem.…”
Section: Restriction Of Diefary Substrates or Precursorsmentioning
confidence: 99%
“…Glutamate, proline and lysine supplements have been suggested as possible treatment for gyrate atrophy although only the last has been tried (11,13,16,57). Acute lysine loads increase plasma lysine levels and the excretion of lysine and ornithine in the urine.…”
Section: Replacement Of Dejicient Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysine and the nonmetabolizable amino acid a-aminoisobutyric acid (AIB) have both been reported to increase renal excretion of the dibasic amino acids (15)(16)(17) and might be useful in GA. Recently, Giordano et al (18) have reported that lysine supplementation diminished plasma ornithine significantly in a child with GA.…”
Section: Introductionmentioning
confidence: 99%